1992
DOI: 10.1152/jappl.1992.73.3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated oxygen deficit increases with inclination of uphill running

Abstract: This study examined whether accumulated oxygen deficit depends on treadmill grade during uphill running. Oxygen uptake was measured during steady-state submaximal running. By linear extrapolation at each grade, energy demand was estimated for short exhaustive runs. Oxygen deficit was the difference between this estimate and accumulated oxygen uptake. Six subjects ran at grades of 1, 15, and 20% (study I), and five males trained for anaerobic metabolism ran at 1, 10.5, and 15% (study II). Accumulated oxygen def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 0 publications
5
36
1
2
Order By: Relevance
“…For each subject, an alternative regression model was established, where an energy equivalent of 3 ml ] accumulation is expected to rise more with incremental inclined grade running, we hypothesized that the [La -] energy equivalent when added to the VO 2 measurements during running exercise would greatly in uence the 10.5% grade running, when compared with level running. It has been shown that grade running demands a high energy turnover 10 , possibly due to a poor running economy 11 . Inclined running imposes a di erent mechanical pattern 12 , as compared with level running and the former pattern relies more on concentric muscle contractions.…”
Section: Figure 1 Depicts the Various Regressions Obtained When Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…For each subject, an alternative regression model was established, where an energy equivalent of 3 ml ] accumulation is expected to rise more with incremental inclined grade running, we hypothesized that the [La -] energy equivalent when added to the VO 2 measurements during running exercise would greatly in uence the 10.5% grade running, when compared with level running. It has been shown that grade running demands a high energy turnover 10 , possibly due to a poor running economy 11 . Inclined running imposes a di erent mechanical pattern 12 , as compared with level running and the former pattern relies more on concentric muscle contractions.…”
Section: Figure 1 Depicts the Various Regressions Obtained When Usingmentioning
confidence: 99%
“…However, it also is apparent that within subjects heavy to severe exercise intensities -such as during an incremental test to exhaustion -eventually lead to increases in total (aerobic + anaerobic) energy costs that are not proportional to increases in work 9 . It is well established that grade running demands a high energy turnover 10 possibly due to a worsening running economy 11 and imposes a different mechanical pattern 12 , as compared with level running. e original studies by M et al [4][5] involved both level and grade treadmill running.…”
Section: Introductionmentioning
confidence: 99%
“…De forma similar, Olesen (1992) constatou que o MAOD de atletas e do grupo-controle era aproximadamente 88 a 92% maior durante a corrida na esteira com a inclinação entre 15 e 20%, quando comparado à inclinação de 1%. Além disso, as diferenças entre esses dois grupos só foram significativas a partir da inclinação de 15%.…”
Section: Outras Variáveis Intervenientesunclassified
“…Segundo esse pesquisador, a redução da eficiência na corrida durante a subida se deve à queda na proporção entre as ações excêntricas e concêntricas realizadas nessa situação, a qual diminuiria a capacidade do músculo esquelético de armazenar energia elástica. Não obstante, naquela ocasião Olesen (1992) não realizou medidas que permitissem sustentar essa relação causal. Bangsbo et al (1993) Com o propósito de testar diretamente a hipótese da influência da massa muscular sobre o MAOD, Sloniger et al (1997) mensuraram a quantidade de massa muscular por meio de imagem de ressonância magnética e do MAOD durante a corrida horizontal ou com a inclinação de 10% na esteira.…”
Section: Outras Variáveis Intervenientesunclassified
“…[12][13][14][15][16] Variable slope uphill running is capable of imposing different relationships between the application of concentric and eccentric forces during the running cycle.…”
Section: ■ Introductionmentioning
confidence: 99%